2338. Early Predictors of Mortality in Neonatal Disseminated Herpes Simplex Virus Infection - Ouellette, Christopher (Open Forum Infect Dis, 2019)
BACKGROUND: Disseminated neonatal herpes simplex virus (dHSV) infection is associated with substantial morbidity and an estimated case fatality rate of ~25% despite antiviral therapy. Contemporary data on predictors of mortality among infants with dHSV infection are limited. METHODS: From January 2012 to December 2018, neonates with HSV infection were identified by the Virology database at Nationwide Children’s Hospital. Demographic, clinical, laboratory, and radiographic data were obtained from the infants’ electronic healthcare records to identify cases of dHSV infection and to determine possible predictor(s) of mortality. dHSV was defined as detection of HSV DNA by polymerase chain reaction (PCR) in blood, cerebrospinal fluid, or skin/eye/mouth, and evidence of hepatitis, pneumonitis, sepsis, or coagulopathy, with or without central nervous system involvement. RESULTS: Of 43 neonates with HSV infection, 12 (28%) infants (median [IQR] age: 8.5 [7–11] days) had dHSV and 6 (50%) died. Clinical and laboratory findings of neonates who survived vs. those who died are presented in Table 1. The median duration of symptoms at presentation was 1.5 [1–2] days. Among infants who died, the median duration of hospitalization to time of death was 1.5 days (range, 0 to 4 days). Clinical signs at presentation and blood semiquantiative viral loads (cycle threshold, Ct) were not different between infants who survived (Ct 18.0 [15.4–23.3]) and those who died (16.6 [13.4–23.3]; P > 0.05). Initial serum alanine aminotransferase (ALT), INR or lactate were not different between the two groups. However, initial serum median albumin concentration was lower among those who died vs. survivors (1.8 g/dL vs. 2.7 g/dL, P = 0.004). To assess the sensitivity and specificity of potential laboratory predictors of mortality, serum laboratory values were evaluated as follows (sensitivity, specificity): ALT > 800 (67%, 80%), INR > 2.7 (67%, 80%), serum lactate > 3 mmol/L (80%, 100%), and initial serum albumin < 2 g/dL (100%, 100%). CONCLUSION: Albumin concentrations < 2 g/dL at presentation correlated highly with mortality in neonatal dHSV infection, suggesting that hypoalbuminemia may reflect components of both viral sepsis and poor synthetic liver function. Larger cohorts of neonates with dHSV infection are needed to confirm this result. [Image: see text] DISCLOSURES: All authors: No reported disclosures.